2009
DOI: 10.1002/jmri.21873
|View full text |Cite
|
Sign up to set email alerts
|

Fast left ventricular mass and volume assessment in mice with three‐dimensional guide‐point modeling

Abstract: Purpose: To investigate the accuracy (vs. standard manual analysis) and precision (scan-rescan reproducibility) of three-dimensional guide-point modeling (GPM) for the assessment of left ventricular (LV) function in mice. Methods:Six male wildtype C57/Bl6 mice (weight 26.2 Ϯ 1.1 g) were scanned twice, 3 days apart. Each scan was performed twice, at 0.2 mm/pixel with one average and at 0.1 mm/pixel with two averages. The 24 studies were anonymized and analyzed in blinded fashion using GPM and standard manual sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 14 publications
(22 reference statements)
2
14
1
Order By: Relevance
“…Earlier MicroCT studies confirmed that quantitative evaluation of global cardiac function is feasible in murine cardiovascular disease models and that pronounced decrease in global heart function takes place soon after LAD artery occlusion. These findings are in agreement with previous reports in that marked reduction in LVSV, LVEF, and CO occurred already on day 1 after occlusion 29,[40][41][42][43] . It is noteworthy to mention that cardiac functional performance is dependent on the type and degree of anesthesia, thus for accurate measurements the heart rate during image acquisition should be kept as physiological as possible 44 .…”
Section: Discussionsupporting
confidence: 83%
“…Earlier MicroCT studies confirmed that quantitative evaluation of global cardiac function is feasible in murine cardiovascular disease models and that pronounced decrease in global heart function takes place soon after LAD artery occlusion. These findings are in agreement with previous reports in that marked reduction in LVSV, LVEF, and CO occurred already on day 1 after occlusion 29,[40][41][42][43] . It is noteworthy to mention that cardiac functional performance is dependent on the type and degree of anesthesia, thus for accurate measurements the heart rate during image acquisition should be kept as physiological as possible 44 .…”
Section: Discussionsupporting
confidence: 83%
“…The analysis time in our study (25 ± 5 minutes) was longer than previously reported values (10 and 8 minutes) using other SASS [42, 43]. Nevertheless, these studies conducted cardiac analysis in mouse heart, thus the number of slices covering the whole heart with the same slice thickness was lower.…”
Section: Discussioncontrasting
confidence: 55%
“…Mice were given subcutaneous buprenorphine (0.8 mg/kg) for pain relief. Six control (male, 26.2 ± 1.1 g) and five mice with 8 weeks old myocardial infarction (female, 24.8 ± 2.2 g) were subjected to CMR (data from full slice analysis of the control mice have been reported previously [6]).…”
Section: Methodsmentioning
confidence: 99%
“…The total imaging time required for the evaluation of LV mass and volume therefore represents a major bottleneck for high throughput evaluation of mouse models. Recently, three-dimensional (3D) guide point modeling (GPM) has been shown to achieve fast evaluation of LV mass and volumes in normal mice [6]. This method enables a 3D geometric model of the LV to be interactively customized to the geometry and motion of the particular animal.…”
Section: Introductionmentioning
confidence: 99%